DIAGNOSIS OF PROBLEMS OF MANAGEMENT OF THE STUDENTS’ INDEPENDENT WORK IN THE INFORMATION AND COMMUNICATION PEDAGOGICAL ENVIRONMENT - Bilousova, L.I.; Kolgatin, O.G.; Kolgatina, L.S. (Journal of Information Technologies in Education (ITE), 2015)
The method of questioning was used in students’ groups to diagnose features of the implementation of independent work in the learning process of pedagogical university. Analysis of the data makes it possible to confirm the usefulness of systematic self-study, identify some causes of difficulties. In particular, students, who often work independently, have higher success in learning,love their future profession; independent work does not replace the classroom ONE, but rather complements it, students, who often work independently, more often attend lectures. Some statistically significant factors that hinder independent work can be distinguished: an overload on other subjects; inertia, laziness; living conditions; the availability of a hobby, which does not coincide with the learning task; family circumstances. Students widely use Internet resources during independent work, but they do it spontaneously and do not obtain proper effect on the success of learning. So management of independent work should be provided special means in information and communication environment, aimed at improving the efficiency of the use of Internet resources during independent work of students.